New insights into pathogenesis of congenital pseudarthrosis of tibia in children using periosteum proteomics analysis. (2nd September 2022) - Liu, Yaoxi; Qin, Zhen Qi; Zheng, Yu; Wu, Jiangyan; Yang, Ge; Tan, Qian; Zhu, Guanghui; Liu, Kun; Mei, Haibo
Abstract : Rationale: The exact etiology and pathogenesis of congenital pseudarthrosis of tibia (CPT) are not clear. Quantitative proteomics analysis plays a vital role in disease pathology research. Tandem mass tag (TMT)‐based proteomics techniques were employed to identify and analyze the differentially expressed proteins (DEP) in the tibia periosteum tissues of CPT patients. Methods: The samples were divided into three groups: CPT with NF1 group, CPT without NF1 group (non‐NF1‐CPT), and control group (patients with open tibial fracture). A fold change ≥1.5 or ≤0.66 and P ‐value <0.05 were used as the thresholds to screen DEPs. Subsequently, bioinformatics resources such as online tools DAVID and String were used to generate gene ontology (GO) annotation, KEGG pathways enrichment, and protein–protein interaction (PPI) network for these DEPs. Results: The results show that a total of 347 proteins were differentially expressed in NF1‐CPT groups, 212 of which were upregulated and 135 were downregulated. There were more DEPs in non‐NF1‐CPT groups; we identified 467 DEPs, including 281 upregulated and 186 downregulated. Among them, NF1‐CPT groups and non‐NF1‐CPT groups shared 231 DEPs, and the remaining 230 DEPs showed the same expression trend in the two disease groups, with 117 upregulated and 113 downregulated. In particular, 116 proteins were altered only in NF1‐CPT groups (94 were upregulated and 22 were downregulated), whereas 236 proteins were altered only in non‐NF1‐CPT groups (164 were upregulated and 72 were downregulated). Finally, compared with non‐NF1‐CPT groups, 47 proteins changed 1.5‐fold and P ‐value < 0.05 in NF1‐CPT groups. Conclusions: To sum up, we found that common DEPS in periosteum of NF1‐CPT and non‐NF1‐CPT groups are mainly involved in cell matrix assembly, cell adhesion, AKT‐PI3K signal pathway activation, and vascular agglutination, which indicate that these are the pathological characteristics of CPT. The osteogenic ability is weak, the osteoclastic ability is strong, the vascular lumen is narrow, the invasive growth and the proliferation of fibroblasts are enhanced in CPT patients.